Rancang Bangun dan Aplikasi Irigasi Tetes Bawah Permukaan Emiter Serabut Kelapa untuk Budidaya Kol Bunga (Brassica oleracea botrytis L.) Dataran Rendah - I Gde Darmaputra; Muhammad Idrus; Surya Surya (Jurusan Teknologi Pertanian, 2014)
The research purposed to design and application of coconut fiber emitter of sub-surface drip irrigation for low land cabbage plant, to determine thickness of coconut fiber emitter that good application for cabbage plant, to measure sub surface-drip irrigation performance that are emitter discharge, wetted area diameter, water use, production and water productivity. This research conducted at State Polytechnic of Lampung from June to November 2013. The results showed that coconut fiber emitter of sub-surface drip irrigation can be applied to cabbage plant. Thickness of coconut fiber emitter that good application for cabbage plant was 15 mm with 10 mm fasteners diameter. Water use of cabbage plant with application of coconut fiber emitter of sub-surface drip irrigation was 0.081 m3 per plant, 38% more efficient than kettle (gembor) irrigation (0.131 m3/plant). Water productivity with coconut fiber emitter of sub-surface drip irrigation was 3.58 kg/m3, 67% more higher than kettle irrigation (2.15 kg/m3). Keywords: design, application, coconut, emitter, drip, irrigation, cabbage.